Early transconjunctival needling revision with 5-fluorouracil versus medical treatment in encapsulated blebs: a 12-month prospective study - Suzuki, Ricardo (2013)
OBJECTIVE: To compare the efficacy of transconjunctival needling revision with 5-fluorouracil versus medical treatment in glaucomatous eyes with uncontrolled intraocular pressure due to encapsulated bleb after trabeculectomy. METHODS: Prospective, randomized, interventional study. A total of 40 eyes in 39 patients with elevated intraocular pressure and encapsulated blebs diagnosed at a maximum five months after primary trabeculectomy with mitomycin C were included. The eyes were randomized to either transconjunctival needling revision with 5- fluorouracil or medical treatment (hypotensive eyedrops). A maximum of two transconjunctival needling revisions per patient was allowed in the needling arm. All patients underwent follow-up for 12 months. Successful treatment was defined as an intraocular pressure ≤ 18 mmHg and a 20% reduction from baseline at the final follow-up. Clinicaltrial.gov: NCT01887223. RESULTS: Mean intraocular pressure at the final 12-month follow-up was lower in the transconjunctival needling revision group compared to the medical treatment group. Similar numbers of eyes reached the criteria for treatment success in both the transconjunctival needling revision group and the medical treatment group. CONCLUSIONS: Despite similar success rates in eyes randomized to transconjunctival needling revision with 5-fluorouracil compared to eyes receiving medical treatment, there was a significantly lower mean intraocular pressure at 12 months after transconjunctival needling revision.